2005
DOI: 10.1002/ijc.21178
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide loss of heterozygosity and its clinical associations in non small cell lung cancer

Abstract: We extensively allelotyped a panel of 71 microdissected primary surgically resected non small cell lung cancer (NSCLC) tumors to identify chromosomal regions that are likely to contain tumor suppressor genes (TSGs) or associated with clinicopathologic and prognostic effects. Loss of heterozygosity (LOH) was detected by genotyping of 177 microsatellite markers and correlation of LOH with clinicopathologic parameters and prognosis was analyzed. Twenty markers showed an LOH frequency greater than 48%, and 8 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 27 publications
(27 reference statements)
3
68
2
Order By: Relevance
“…However, the increase in resolution using high-density SNP arrays combined with laser microdissection enabled us to identify regions that have not previously been related to this disease, including a 2.9-Mb region showing LOH at chromosome 21q22.2 in 30% of the samples. Loss of 21q22 has previously been reported in gastric cancer and NSCLC (Park et al, 2000;Tseng et al, 2005), but the LOH region we discovered in PCa at 21q22.2 is more distant and therefore previously unknown in relation to carcinomas. Recently, Tomlins et al (2005) identified a highly frequent recurrent gene fusion in PCa, including ERG and TMPRSS at chromosome 21q22, and was recently confirmed by Yoshimoto et al (2006).…”
Section: Discussionmentioning
confidence: 51%
“…However, the increase in resolution using high-density SNP arrays combined with laser microdissection enabled us to identify regions that have not previously been related to this disease, including a 2.9-Mb region showing LOH at chromosome 21q22.2 in 30% of the samples. Loss of 21q22 has previously been reported in gastric cancer and NSCLC (Park et al, 2000;Tseng et al, 2005), but the LOH region we discovered in PCa at 21q22.2 is more distant and therefore previously unknown in relation to carcinomas. Recently, Tomlins et al (2005) identified a highly frequent recurrent gene fusion in PCa, including ERG and TMPRSS at chromosome 21q22, and was recently confirmed by Yoshimoto et al (2006).…”
Section: Discussionmentioning
confidence: 51%
“…LOH in 6p22-23-detected in more than 30% of penile carcinoma in this study-has also been shown in cervix carcinoma, 20,24 nonsmall cell lung cancer 25 or ovarian cancer, 26 although no correlations to advanced stages or survival could be established. LOH in microsatellite loci D6S260 and D6S1267 is in this study frequently associated with occurrence of metastases and poor prognosis.…”
Section: Discussionsupporting
confidence: 43%
“…Marsit et al 12 reported that LOH at 9p13 was a significant predictor of improved survival, whereas the homozygous deletion was associated with poor survival in 100 squamous cell carcinoma/adenocarcinoma patients undergoing surgical resection. Tseng et al 21 linked LOH at 1p36.23 with smoking, squamous carcinoma, and late-stage disease. Furthermore, LOH at q37.3 and 6p21-p22 were significantly associated with poor prognosis in squamous cell carcinoma/adenocarcinoma patients, using both univariate and multivariate Cox regression analyses.…”
Section: Genetic Changesmentioning
confidence: 99%